Benign tumors broaden the field of application for immunotherapy - Youssef, Mohamed A.; Al-Sharif, Hisham; McGrath, Brian T.; Picken, Maria M.; Le Poole, I. Caroline (Frontiers in Immunology, 2025)
Immunotherapy has shown significant potential for treating malignancies. Not yet widely considered is the opportunity to employ immunotherapy for the treatment of benign tumors. By focusing on targetable antigens expressed following specific genetic changes associated with individual benign tumors, immunotherapy may provide an effective approach to benign tumor treatment, circumventing the need for more conventional surgery. Immunotherapies can specifically recognize and target tumor cells, which could be especially beneficial for benign tumors given the extended timeframe available for treatment. Thus, benign tumors, offering a greater window of opportunity for treatment and a relatively stable phenotype associated with a limited mutation burden, can derive great benefit from immunotherapeutic approaches targeting antigens uniquely associated with each condition.